A Record of the Ratan Goby, Ponticola ratan (Gobiidae, Perciformes), in the Dneprodzerzhinsk Reservoir (Dnieper River) - Manilo, L.G.; Didenko, A.V. (Вестник зоологии, 2013)
The paper contains new data, which confirms distribution of the ratan goby, Ponticola ratan (Nordmann, 1840), in fresh waters, as well as its diagnosis, description, and brief information on its biology. Приведены новые данные, подтверждающие распространение бычка-ратана, Ponticola ratan (Nordmann, 1840), в пресных водах, а также его диагноз, описание, краткие сведения по биологии.